قضايا الجزائر من خلال جريدة الإقدام للأمير خالد الجزائري(1919-1923م) - فاطمة الزهرة تقار; د/ فاطمة دجاج (جامعة عمار ثليجي الاغواط, 2023)
الملخص: تعد جريدة" الإقدام" 1919-1923 إحدى أبرز الجرائد الوطنية التي ظهرت مباشرة بعد الحرب العالمية الأولى، وهي لسان حال الأمير خالد، وتعتبر من بين الوسائل التي اتخذها لشرح أفكاره، حيث تعتبر همزة وصل بينه وبين مؤيديه، كما تعد أيضا سلاح ً ضد خصومه السياسيين، وسعى عبرها الى توحيد القوى الوطنية لدفاع عن حقوق المدنية والسياسية لمسلمي شمال افريقيا ، ورغم قصر عمرها، إلا أنها استطاعت أن تعبر عن مجمل الانشغالات المتعلقة بالجزائريين، كان الأمير خالد له دور البارز في إظهار الإهتمام بالجزائريين ومكافحة الإستعمار، وقد كان اهتمامه يشمل مختلف المجالات سواء كانت سياسية أو ثقافية أو عسكرية، وبدأ شغفه بعالم صحافة والنضال بالقلم نتيجة ادراكه التام بأن مواجهة فرنسا عن طريق القلم الصحفي أنجح لفضح جرائمها وإيصال أصوات الأهالي المستضعفين، حيث كان يستغل منابر الحرب الإعلامية للدفاع عن الأهالي بجميع فئاتهم. وقام بطرح قوي للقضايا الجزائرية ذات وزن ثقيل على الملأ بخصوص جرائمهم ضدهم، حيث كانت المرآة تعكس صورة الحقيقية للوجود الإستعماري بالجزائر.. Summary: The newspaper L'ikdam 1919-1923 is one of the most prominent national newspapers to emerge immediately after the First World War, the tongue of Amir Khaled.It is one of the means he has taken to explain his ideas, as it is a link between him and his supporters, and it is also a weapon against his political opponents.Through it, he sought to unite national forces to defend North African Muslims' civil and political rights,Although she was short-lived, she was able to express all the concerns about Algerians. Amir Khalid played a prominent role in demonstrating interest in Algerians and in the fight against colonialism, and his interest encompassed various areas,whether political, cultural or military,His passion for the world of journalism and the struggle for the pen began as a result of his full realization that confronting France through the press pen was more successful in exposing its crimes and communicating the voices of the Vulnerable communities.He used media war platforms to defend all categories of people.He brought Algeria's heavyweight cases to the public for their crimes against them,The mirror reflected the true image of Algeria's colonial existence.